Enantioselective determination of (R)‐ and (S)‐lansoprazole in human plasma by chiral liquid chromatography with mass spectrometry and its application to a stereoselective pharmacokinetic study. Issue 21 (30th September 2015) - Sun, Luning; Cao, Yang; Jiao, Huiwen; Fang, Yunqian; Yang, Zhicheng; Bian, Mingliang; Zhang, Hongwen; Gong, Xiaojian; Wang, Yongqing
<x xml:space="preserve">Abstract</x> A simple and enantioselective method was developed and validated for the simultaneous determination of (R)‐ and (S)‐lansoprazole in human plasma by chiral liquid chromatography with tandem mass spectrometry. Lansoprazole enantiomers and internal standard (esomeprazole) were extracted from plasma using acetonitrile as protein precipitating agent. Baseline chiral separation was achieved within 9.0 min on a Chiralpak IC column (150 mm × 4.6 mm, 5 μm) with the column temperature of 30°C. The mobile phase consisted of 10 mM ammonium acetate solution containing 0.05% acetic acid/acetonitrile (50:50, v/v). The mass spectrometric analysis was performed using a QTrap 5500 mass spectrometer coupled with an electrospray ionization source in positive ion mode. The multiple reactions monitoring transitions of m/z 370.1→252.1 and 346.1→198.1 were used to quantify lansoprazole enantiomers and esomeprazole, respectively. For each enantiomer, no apparent matrix effect was found, the calibration curve was linear over 5.00–3000 ng/mL, the intra‐ and inter‐day precisions were below 10.0%, and the accuracy was –3.8 to 3.3%. Analytes were stable during the study. No chiral inversion was observed during sample storage, preparation procedure and analysis. The method was applied to the stereoselective pharmacokinetic studies in human after intravenous administration of dexlansoprazole or racemic lansoprazole.